Who Are You Calling Irrational? Marginal Costs, Variable Costs, and the Pricing Practices of Firms - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2009)
Economists sometimes decry the persistence with which firms set prices above marginal cost and thus, according to the economists, fail to maximize profits. But it is the economists who have it wrong – first, because variable accounting costs are not always a good proxy for marginal economic costs, but more importantly because in an industry with U-shaped cost curves, a firm at a long-run sustainable equilibrium faces increasing marginal costs – i.e., a rising shadow price on some constrained input – i.e., in general, acost of capital. A corollary is that in such an industry the equilibrium mark-up over variable cost varies directly with capital intensity.
Keywords: B21; D24; D43; K21; L11; L40; 330; market power; price; mark-up; marginal cost; variable cost